The application of think pair share cooperative learning strategies to improve English learning outcomes in elementary schools - Amalia, Rizka Afni; Yuliandari, Mela Rafika; Kautsar, Faustinina (Prosiding University Research Colloquium, 2021)
This study aims to describe the activities of teachers and students, mastery of students' critical thinking skills, improve English learning outcomes through think pair share cooperative learning strategies in elementary schools. The researcher found that the thinking skills of students were very lacking, this could be seen from the number of students who could not respond to every statement made by the teacher. This study uses a quantitative descriptive method The object of research is the improvement of learning outcomes which include learning outcomes of knowledge and skill competencies. To measure the results of learning English, students used multiple choice learning outcomes tests for knowledge learning outcomes and speaking skills tests to measure skills learning outcomes given at the end of each cycle. It can be concluded that the use of learning strategies that are in accordance with the type of TPS can further develop students' thinking skills in English subjects in elementary schools.